Micro Foundations of Macroeconomic Price Adjustment: Survey Evidence from Swedish Firms - Mikael Apel; Richard Friberg; Kerstin Hallsten (Sveriges Riksbank, 2001)
This paper reports the results from a survey on price-setting behavior of a large random sample of Swedish firms. Prices are found to adjust only infrequently; the median firm adjusts the price once a year. State-dependent pricing is found to be more common than is usually assumed and at least as important as time-dependent pricing. The paper sums up the evidence from this and two similar large-scale surveys on UK and US data. Notably, and suggesting directions for further research, four of the theories of price rigidity are ranked by the respondents among the top-five places in all three studies.
Keywords: D40; E30; L11; 330; Nominal rigidity; Price-rigidity; Price-setting; Real rigidity; Time-dependent pricing; State-dependent pricing